Adverse effects of falciparum and vivax malaria and the safety of antimalarial treatment in early pregnancy: a population-based study. - Mcgready, R; Lee, S; Wiladphaingern, J; Ashley, E; Rijken, M; Boel, M; Simpson, J; Paw, M; Pimanpanarak, M; Mu, O; Singhasivanon, P; White, N; et al. (2012)
BACKGROUND: The effects of malaria and its treatment in the first trimester of pregnancy remain an area of concern. We aimed to assess the outcome of malaria-exposed and malaria-unexposed first-trimester pregnancies of women from the Thai-Burmese border and compare outcomes after chloroquine-based, quinine-based, or artemisinin-based treatments. METHODS: We analysed all antenatal records of women in the first trimester of pregnancy attending Shoklo Malaria Research Unit antenatal clinics from May 12, 1986, to Oct 31, 2010. Women without malaria in pregnancy were compared with those who had a single episode of malaria in the first trimester. The association between malaria and miscarriage was estimated using multivariable logistic regression. FINDINGS: Of 48,426 pregnant women, 17,613 (36%) met the inclusion criteria: 16,668 (95%) had no malaria during the pregnancy and 945 (5%) had a single episode in the first trimester. The odds of miscarriage increased in women with asymptomatic malaria (adjusted odds ratio 2·70, 95% CI 2·04-3·59) and symptomatic malaria (3·99, 3·10-5·13), and were similar for Plasmodium falciparum and Plasmodium vivax. Other risk factors for miscarriage included smoking, maternal age, previous miscarriage, and non-malaria febrile illness. In women with malaria, additional risk factors for miscarriage included severe or hyperparasitaemic malaria (adjusted odds ratio 3·63, 95% CI 1·15-11·46) and parasitaemia (1·49, 1·25-1·78 for each ten-fold increase in parasitaemia). Higher gestational age at the time of infection was protective (adjusted odds ratio 0·86, 95% CI 0·81-0·91). The risk of miscarriage was similar for women treated with chloroquine (92 [26%] of 354), quinine (95 [27%) of 355), or artesunate (20 [31%] of 64; p=0·71). Adverse effects related to antimalarial treatment were not observed. INTERPRETATION: A single episode of falciparum or vivax malaria in the first trimester of pregnancy can cause miscarriage. No additional toxic effects associated with artesunate treatment occurred in early pregnancy. Prospective studies should now be done to assess the safety and efficacy of artemisinin combination treatments in early pregnancy.